Feasibility of using simulated patients for onsite structured practice feedback in Jordanian community pharmacy settings - Eman A. Hammad; Eman Elayeh; Deema Jaber; Ibrahim Abu mustafa; Sinaa Al-Aqeel (Elsevier, 2022)
Simulated patient (SP) visits followed with structured feedback is useful to outline training needs as well as preference for continuing professional education in community pharmacy settings. This study aimed to investigate community pharmacists' management of an over-the-counter (OTC) product request and feasibility of immediate SP feedback in Jordan. Four trained SP visited a sample of pharmacies in three main urban cities in Jordan requesting an antacid. Information request and professional behavior as well as content of information were evaluated. The SP provided structured immediate feedback. The pharmacy staff views on the visit and usefulness of the feedback were collected. A total of 57 visits were conducted. The average duration of SP visits was 1.55 min. The average score (±SD) for information seeking behavior was 16% (±7) and for professional behavior was 56% (±15). The average score for information provision provided spontaneously was 17.1% (±12). Upon demand by the SP; the average score for information improved to 47.6 (±18). Non-pharmacological advice was not offered often; only 6 (10.5%) visits. Written information was provided in 10 (17.5%) visits. Immediate feedback was accepted by all visited pharmacies. Participants expressed positive views about the SP visit and usefulness of the feedback. Community pharmacists supplied OTC drug without carful screening of symptoms and essential information. The SP approach with immediate feedback was shown feasible and well accepted. Further potential for use of SP with feedback formally in practice and professional development should be explored in future studies.